ANALISIS PERSPEKTIF MAHASISWA PENDIDIKAN BIOLOGI MENGENAI PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERFIKIR KRISTIS - Dealova Sihite, Yolanda; Panjaitan , Anisali; Monita Silalahi, Ester Tania; Simorangkir , Celine Agustina; Arwita, Widya; Mukra, Rizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the perspectives of Biology Education students on the implementation of the Problem Based Learning (PBL) model in biology learning. The research employed a descriptive qualitative approach with 27 students of Biology Education at Universitas Negeri Medan, cohort 2023, selected using total sampling technique. Data were collected using a Likert-scale questionnaire covering aspects of understanding, experience, benefits, constraints, and the effectiveness of PBL, and then analyzed using descriptive statistics in the form of percentages. The results showed that 44.44% of respondents strongly agreed and 37.04% agreed, resulting in a total positive response of 81.48%, which falls into the very positive category. PBL is considered effective in improving students' understanding of biological concepts, critical thinking skills, problem-solving abilities, and collaboration. However, several challenges were identified, including time constraints, lack of participation among some group members, and difficulties in understanding complex problems. Therefore, it can be concluded that the implementation of PBL is well-received and has the potential to improve the quality of biology learning, although improvements in its implementation are still needed.